MANIS: protocolo de análise de casos de inovação social de acordo com os 17 objetivos do desenvolvimento sustentável - Assis, Geovana Blayer Ribeiro de (2020)
This research analyzes the Social Innovation (SI) phenomena as a potential agent of transformation in emerging contexts, marked by accelerated urban growth and by several social, economic and / or environmental problems. The study investigates the possible fields of application of Social Innovation and what has been its effective positive impact in these contexts, especially with regard to social improvements and their contributions to Sustainability, as well as their association with the 17 Sustainable Development Goals of UN, which must be met by the year 2030. Therefore, the research aims to expand the studies on Social Innovation and develop a protocol for analyzing promising cases. This protocol, known as MANIS, aims to better understand how a case of Social Innovation is classified, what are the main factors that define this case as “success”, that is, the benefits generated by the SI proposal, as well as its relations with the dimensions of Sustainability and the 17 UN SDGs. To this end, the study used theoretical references from protocols for the identification of already existing cases of Social Innovation, to analyze the applicability in other SI experiences. Based on an exploratory study with a qualitative approach, the research involved stages of: literature review, case studies with questionnaires, panel with SI specialists and the proposition of the MANIS protocol. The results obtained are materialized mainly in the final document that should serve as an academic reference in the identification and analysis of cases of Social Innovation and its relationship with the Sustainable Development Goals. In addition, given the need for further studies on Social Innovation, the MANIS protocol will enable a greater experiences diffusion.